2014
DOI: 10.5897/ajb2014.13944
|View full text |Cite
|
Sign up to set email alerts
|

Pequi pulp (Caryocar brasiliense Cambess): Drying kinetics and thermodynamic properties

Abstract: The objecti Cambess) Eleven mat were fitted of Pequi fru Pequi pulp. (m 2 s-1) for t 7694.94 J m and 4925.13 251.01,-250 free energy consistent t of water wit Key words: TRODUCTION qui (Caryoca a typical fruit f h high nutritio the regional eparation of ditional dishe oughout Braz 2013).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
3
2
2
Order By: Relevance
“…Gibbs free energy is related to the work required to make the sorption sites available, and its positive value indicates an endergonic reaction, in which the addition of energy to the air is necessary for drying of the product (Nkolo Meze'e et al, 2008). Silva et al (2014), Rodovalho et al (2015), and also reported this behavior.…”
Section: Resultssupporting
confidence: 57%
“…Gibbs free energy is related to the work required to make the sorption sites available, and its positive value indicates an endergonic reaction, in which the addition of energy to the air is necessary for drying of the product (Nkolo Meze'e et al, 2008). Silva et al (2014), Rodovalho et al (2015), and also reported this behavior.…”
Section: Resultssupporting
confidence: 57%
“…The effective diffusion coefficient is directly influenced by an increase in the temperature, because this change modifies the water removal from the product. This result was also reported by Silva et al (2014) and Sousa et al (2017). Madamba et al (2003) highlighted that the effective diffusion coefficients are of the order of 10 -11 to 10 -9 m² s -1 for food products.…”
Section: Abcsupporting
confidence: 89%
“…Madamba et al (2003) highlighted that the effective diffusion coefficients are of the order of 10 -11 to 10 -9 m² s -1 for food products. The values found for pequi mesocarp were lower (around 10 -11 ) compared with the work of Sousa et al (2017) at 50-80 °C temperatures (of the order of 10 -8 ), and higher than previously reported by Silva et al (2014) Differences in diffusivity may be caused by the chemical composition of the products, such as lipid content, initial moisture content and primarily, size, geometric format and the structure of each material. Physical and chemical properties depend on the composition and play an important role in the water migration rate from the inside to the surface of the product, owing to greater or lesser affinity, as well as the structural nature of the material (Khan et al, 2016).…”
Section: Abccontrasting
confidence: 69%
See 1 more Smart Citation
“…The difference between the model fitted by these authors and the one in the present study may be due to the different relative moisture ranges in the experiments, as well as to the model selection criterion used by these authors (only evaluation of coefficient of determination -R 2 ). There was a linear increase in the effective diffusion coefficients with the increment in temperature, which indicates greater magnitude of water transfer from inside to the periphery of the product (Figure 2), as demonstrated by Silva et al (2014), Oliveira et al (2014a) and Smaniotto et al (2017).…”
Section: Resultsmentioning
confidence: 49%